Differentiated effects and mechanisms of N-, P-, S-, and Fe-modified biochar materials for remediating Cd- and Pb-contaminated calcareous soil - Amir Bostani; Xingying Meng; Le Jiao; Srđan D. Rončević; Peng Zhang; Hongwen Sun (Ecotoxicology and Environmental Safety)
To investigate the remediation effects of various modified biochar materials derived from different impregnation agents on Cd- and Pb-contaminated calcareous soil, nitrogen (N-), phosphorus (P-), sulfur (S-), and iron (Fe-) modified biochar materials (NBC, PBC, SBC, FBC) were fabricated through the impregnation-pyrolysis method and employed to immobilize Pb and Cd in the calcareous soil. The characterization results showed that NBC exhibited an uneven pore size distribution and increased aromaticity, while PBC and SBC had increased pH and ash content. Pot experiments demonstrated significantly different effects of various modified biochar materials on soil immobilization and plant uptake of Cd and Pb. With regard to soil pH, FBC caused a notable decrease in both rhizosphere and non-rhizosphere areas, while the other materials showed an increase. NBC, PBC, and SBC effectively immobilized Cd and Pb in the soil and significantly reduced their accumulation in Chinese cabbage by 34.4 %-58.9 % for Cd and 9.2 %-53.1 % for Pb, with PBC having the best effect, attributed to complexation, precipitation, and adsorption. However, FBC had strong acidity and poor immobilization ability, which increased the available concentrations of Cd and Pb in the soil. Additionally, PBC promoted the growth, enzyme activity, and tolerance to Cd- and Pb-contaminated soil of Chinese cabbage. Overall, NBC and PBC were identified as the most effective modified biochar materials for stabilizing Cd and Pb in the soil, reducing heavy metal uptake by Chinese cabbage, and boosting enzyme activity.